CULTURAL CONTENT ANALYSIS OF ENGLISH LEARNING MATERIALS AT FOUR SENIOR HIGH SCHOOLS IN BANDAR LAMPUNG - Anggia, Helta; Verawati, Noning; Vandika, Arnes Yuli (English Education: Jurnal Tadris Bahasa Inggris, 2018)
High interest of Bandar Lampung citizen in mastering English communication has made many English learning centers appearing with various methods and learning approaches. One of the approaches used by those centers in teaching English is that students learn English using the cultures of countries where the English language comes from. However, in the Indonesian context, English learning materials are spread within various cultures types, information, senses, and elements. This fact urges this study to analyze the cultural contents of four textbooks of four different high schools in Bandar Lampung, Indonesia in order to map how cultures play role in Indonesian ELT context especially ELT in Bandar Lampung. The data gathering techniques used are Interview, Questionnaire, and Senior High School English textbooks analysis. The results conclude that target cultures, contextual writing tasks, aesthetic sense and products (Silvia, 2014&Adaskou et.al., 1990) dominate the English textbooks so that this finding represents the culture involvement in English language teaching of senior high schools in Bandar Lampung context.Keywords: English Language, local culture, a learning method